Rematriating the Archipelago: A Gendered Environmental History of Kodiak - Thorne, Laurel (Matrix, 2026)
This paper draws on Alutiiq oral legends and histories to craft a gendered environmental history of the Kodiak Archipelago from the perspective of Alutiiq women, examining their relationships with the island environment and their roles within it. Alutiiq women were stripped of their autonomy over their reproductive and environmental roles under Russian and American colonization. However, Alutiiq values, including Nunapet, Nunapet Carliarluki, and Unguwacirpet, endured, linking women's physical health to land stewardship. Alutiiq women historically led hunting festivals, prepared fish and skins, and controlled their reproductive lives through breastfeeding and midwifery. Today, Alutiiq women reclaim environmental values through crafts and birthing practices, embodying what Cutcha Risling Baldy calls "(re)righting and (re)riteing Indigenous epistemologies." Their survival and revival demonstrate how Alutiiq women resisted colonialism and sustained reciprocal relationships with the environment.